Society and underreporting of child abuse cases in Malaysia: Theoretical consideration - Abdullah, Jamhirah; Hitam, Mizan; Ra'ees, Wahabuddin; Eissa, Garoot Suleiman; Ibrahim, Nabila Huda (IDOSI Publications, 2017)
Child abuse has been a long-standing social problem in Malaysia. The increase in child abuse cases has become worrisome and causes undesirable cost and social burden. Social awareness, educated society towards child abuse, legislative and policy remedies, and financial help are the measures that should be considered to prevent child abuse. Evidences suggest that child abuse cases in Malaysia are underreported. Only a fraction of the total number of child abuse cases is reported. Academics argue that society can play an important role in prevention and reporting of child abuse. Involvement of social groups, community leaders and every member of society in prevention and reporting of child abuse will reduce child abuse cases in the country.